PERAN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN - Fitrah, Muh. (Jurnal Penjaminan Mutu, 2017)
This writing has main purpose that is to know head master’s role in improving educational quality, leadership, duty, and headmaster’s role in improving educational quality, leardership, duty, and headmaster’s role in order to produce process and product of quality education. Educational quality is our hope in facing strict life exchange in several sectors especially in education sectors for better future. For the sake of making educational quality, this needs role of leaders in educational institutes. One of them is headmaster because it is the pioneer is moving all changes to go to educational quality. Headmaster’s duty is not only leading ceremony, waiting incoming letter to be signed but also making a good quality of education in school. Specifically headmaster’s role in improving quality of education are doing monitoring, evaluating continually toward seccessful program determined, planning and arranging word plan agreed with improving needs of educational quality which orients on school’s mission, making intensive commumication with teachers, students, student’s parents and society.